Physique Artistry. (London : Lon of New York, 1957)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : driemaandelijks
Redactie : Lon of New York, Suite 35A, 119 Oxford Street, London W1
Engels
Periodiek